Suitability of lock-in infrared thermography for luminescent glass development. Issue 2 (2nd April 2020) - Nolte, Peter W.; Ziegeler, Nils; Rimbach, A. Charlotte; Schweizer, Stefan
ABSTRACT: The purpose of this work is to evaluate the suitability of lock-in infrared thermography for luminescent glass development. Lithium borate glass of different composition is fabricated and studied to detect changes in the thermal diffusivity as the composition changes and property modifiers are introduced. In addition, the effect of terbium doping on the thermal diffusivity of the glass is studied.